Assessment of inter-relationships between yield and yield attributes in safflower (Carthamus tinctorius L.): Assessment of inter-relationships between yield and yield attributes in safflower (Carthamus tinctorius L.) - C MANIKYA MINNIE,; C SUDHAKAR,; T RAJESHWAR REDDY,; C SUDHA RANI , (Journal of Oilseeds Research, 2023)
Character association studies in 29 genotypes of safflower for seven characters conducted at Agricultural Research Station, Tandur revealed significant positive association of single plant yield with test weight, number of effective capitula per plant, plant height and number of seeds per capitulum. Estimates of direct and indirect effects of component characters on single plant yield at genotypic level revealed that test weight contributed for maximum positive direct effect on single plant yield followed by days to maturity, plant height and number of seeds per capitulum. Also, these traits had positive and significant association with grain yield. Critical analysis of character association and path analysis showed that these characters should be given importance to isolate superior lines with genetic potentiality for high grain yield.